ANALISIS PENGARUH MANAJEMEN RISIKO KREDIT TERHADAP KOLEKTIBILITAS KREDIT MODAL KERJA PADA BPR ABDI WARGA MULIA - Jerry Rizaldi Putra (Yayasan Nusantara Hasana Berdikari, 2026)
This study aims to analyze the effect of credit risk management based on the 5C principles (Character, Capacity, Capital, Collateral, Condition) and the 3R principles (Return, Repayment, Risk Bearing Ability) on Non-Performing Loans (NPL) at BPR Abdi Warga Mulia. The research method used is a quantitative approach with multiple linear regression analysis. Data were obtained through questionnaires distributed to 100 respondents of working capital loan customers as well as documentation of non-performing loan reports. The results show that partially, the variables Character (X1), Capacity (X2), Capital (X3), Return (X6), Repayment (X7), and Risk Bearing Ability (X8) have a significant effect on NPL with significance values < 0.05. Meanwhile, Collateral (X4) and Condition (X5) do not significantly affect NPL (p > 0.05). Simultaneously, the 5C and 3R principles significantly influence NPL with an F-statistic = 41.27 > F-table = 2.12 and significance = 0.000. The coefficient of determination (R²) is 0.715, indicating that 71.5% of the variation in NPL can be explained by the 5C and 3R variables, while the remaining 28.5% is explained by other factors outside the research model. It can be concluded that the application of credit risk management based on the 5C and 3R principles plays an important role in reducing the level of NPL at BPR Abdi Warga Mulia. Therefore, the bank needs to strengthen the assessment of character, business capacity, capital, and repayment discipline to maintain loan quality and minimize the potential occurrence of non-performing loans.